2002
DOI: 10.1144/sjg38020069
|View full text |Cite
|
Sign up to set email alerts
|

Conodont biostratigraphy of the Crawford Group, Southern Uplands, Scotland

Abstract: Synopsis Extensive new conodont collections from the Crawford Group, the oldest succession in the Southern Uplands of Scotland, support the previously documented biostratigraphical ages for the included formations. The Raven Gill Formation is lower Whitlandian, Arenig (comparable in age to the Dounans Limestone in the Highland Border Complex) and the Kirkton Formation is latest Llandeilian-Aurelucian, Llanvirn to Caradoc in age. It is concluded that there is a significant stratigraphical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In addition, based on a poorly preserved, less diverse radiolarian assemblage, Danelian (1999) tentatively correlated the same chert sequences with the Haplentactinia juncta -Inanigutta unica zone which was described from eastern Kazakhstan. The assemblage reported here can be placed within the P. anserinus conodont zone with confidence, as the fauna described comes from strata in the same area that were previously described by Armstrong et al (1990Armstrong et al ( , 2002 and Danelian (1999) (Fig. 2a).…”
Section: Biostratigraphic Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, based on a poorly preserved, less diverse radiolarian assemblage, Danelian (1999) tentatively correlated the same chert sequences with the Haplentactinia juncta -Inanigutta unica zone which was described from eastern Kazakhstan. The assemblage reported here can be placed within the P. anserinus conodont zone with confidence, as the fauna described comes from strata in the same area that were previously described by Armstrong et al (1990Armstrong et al ( , 2002 and Danelian (1999) (Fig. 2a).…”
Section: Biostratigraphic Discussionsupporting
confidence: 80%
“…The conodonts Pygodus anserinus and Periodon aculeatus constrain the age of the chert sequences in the Hawkwood Burn in the Kirkton Formation to the latest Darriwilianearliest Sandbian (late Llanvirnianearly Caradoc in terms of British series) (Armstrong et al 1990(Armstrong et al , 2002Danelian & Floyd, 2001). In addition, based on a poorly preserved, less diverse radiolarian assemblage, Danelian (1999) tentatively correlated the same chert sequences with the Haplentactinia juncta -Inanigutta unica zone which was described from eastern Kazakhstan.…”
Section: Biostratigraphic Discussionmentioning
confidence: 99%
“…It is a common component in collections from the Baltic region (Lindstrom 1955;Van Wamel 1974;Lofgren 1978;Tolmacheva & Lofgren 2000), and is known from Kazakhstan (Dubinina 1991;2000). Occurrences in Britain include the Crawford Group at Ravengill Burn in the Southern Uplands (Lamont & Lindstrom 1957;Armstrong et al 2002) and the North Esk locality as reported here. It has been described from many localities around the margins of Laurentia, for example Cow Head Group, western Newfoundland (Fahraeus & Nowlan 1978;Stouge & Bagnoli 1988;Pohler 1994;Williams et al 1994;Johnston & Barnes 1999;2000), Deep Kill Shale, eastern New York (Landing 1976), Jutland Klippe in northern New Jersey (Repetski et al 1995), Hamburg Klippe, central Pennsylvania Repetski 1984), Mazarn Shale, Ouachita Mountains, central Arkansas (Chludzinski 1993), Ninemile Formation, Antelope Range, Eureka County, Nevada (Ethington 1972) and Kechika Formation, northeastern British Columbia (Pyle & Barnes 2002).…”
Section: Age and Environmental Implications Of P Gracilismentioning
confidence: 68%
“…2009; Sheridan & Bickford 2011), and offshore migration of conodonts during their development (e.g. Armstrong & Dean 1996; Dingle & Drake 2007).…”
Section: Discussionmentioning
confidence: 99%